Branding Strategies to Enhance the Appeal of Cultural Heritage Sites for International Tourists - Iswanto, Dedy; Irsyad, Ziqrurrahman; Sudarta; Fuzail, Muhammad; Gamri, Muhammad (PROCURATIO: Jurnal Manajemen & Bisnis, 2025)
Purpose – This study explores the application of branding in enhancing the attractiveness of cultural heritage sites for international tourists. It investigates the role of branding in shaping tourist perceptions, increasing revisit intention, and improving visitor satisfaction. Design/method/approach – A Systematic Literature Review (SLR) was conducted using literature from Scopus, DOAJ, and Google Scholar. Keywords like "branding," "cultural heritage sites," "tourist attraction," and "tourist perception" were used to select studies published between 2014-2024. Findings – Effective branding strategies, including authentic brand images, experiential marketing, and emotional attachment through historical nostalgia, positively influence tourists’ perceptions and satisfaction. Branding also contributes to local tourism growth and job creation. However, challenges such as information overload and commercialization, which may compromise cultural values, remain. Digital technologies enhance global visibility and cultural narratives. Implications – The study underscores the need for balancing commercial appeal and cultural preservation in branding strategies. Policymakers and tourism managers should focus on authentic branding to attract and retain international tourists. Novelty/Originality – This research offers new insights into how branding influences cultural heritage tourism, particularly regarding the role of digital technologies and the challenges of over-commercialization.